(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Depression is one of the most common psychiatric disorders with global public health concern that is linked to systemic inflammation. The monocyte to lymphocyte (MLR) and platelet to lymphocyte ratio (PLR) are partially new markers which may be evaluated with simple blood test and which are shown to be highly informative in showing chronic low grade inflammation associated with pathophysiology of depressive disorder. Objective: To evaluate the relation of MLR and PLR between patients with depression according to severity of disease. Methods: This observational study was conducted in the Department of Psychiatry of Jahurul Islam Medical College Hospital (JIMCH), Bajitpur, Kishoregonj between November 2012 and April 2013. Subjects between the age group of 25 and 55 were included in the study that involved 253 subjects with diagnosed depressive disorder according to the criteria of Diagnostic and Statistical Manual of Mental Disorders, Revised Text (DSM IV-TR) who received no pharmacological therapy of depression within the past 01 month. A sociodemographic information form and the Hamilton Rating Scale for depression (HAM-D) were administered. Patients were classified into four groups according to their HAM-D score such as mild, moderate, severe, and very severe depression. Blood sample were taken for biochemical analysis and complete blood parameters were evaluated in the hematology laboratory of JIMCH. All data were expressed as mean±SD. For statistical analysis, Chi-square test (χ2) was used to compare categorical variables, frequencies, and ratios. An independent sample ‘t’ test was used to compare normally distributed variables between two groups. Results: In the present study, it was found significant differences in the MLR, PLR, monocyte, leukocyte values of the patient group with depression according to severity of disease. Severe and very severe depression had significantly higher MLR levels compared to patients with mild and moderate depression. On the other hand, mild and moderate depression. On the other hand, mild and moderate depression had significantly higher PLR levels compared to patients with severe and very severe depression. Conclusion: In summary, the findings of the study reveal that higher HAM-D scores are associated with higher MLR and lower PLR levels in patients with depressive illness compared to patients with lower HAM-D scores. Moreover, a high MLR values supports the view that inflammation is a critical factor in the etiology of depression. JAFMC Bangladesh, Vol 19, No 2 (December) 2023:12-15.